Opioid Use after Transforaminal Lumbar Interbody Fusion: A Comparison between Open and Minimally Invasive Surgery - Abaunza-Camacho, Juan Felipe; Gomez-Niebles, Sara; Madrinan-Navia, Humberto; Aponte-Caballero, Rafael; Riveros, William Mauricio; Laverde-Frade, Leonardo (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2024)
Background Opioids are medications frequently used in patients with moderate and severe chronic pain. Their pharmacologic profile allows their use in acute severe postoperative pain. However, due to their highly addictive profile, opioid misuse is considered a public health issue. Vertebral spine fusion, decompression, and instrumentation are often associated with acute, severe postoperative pain. The present study aims to compare postoperative opioid consumption in a group of patients who underwent open transforaminal lumbar interbody fusion (OTLIF) against a similar group of patients who underwent minimally invasive transforaminal lumbar interbody fusion (MTLIF).Methods We present a quantitative, observational, analytical, and historical cohort study. After convenience sampling, we identified 45 patients, 34 of whom underwent OTLIF and 11 underwent MTLIF. The analysis was made after measuring the following variables: demographics, type of surgery, length of stay, pain control, opioid type, and opioid dose. Statistical methods were implemented according to the origin and behavior of the variable.Results We found a difference between significant and nonsignificant pain among the groups with less opioid consumption in the MTILF group. This difference was seen in the frequency and dosage during all observation periods. However, in the postoperative observation, the frequencies and dosages were equal between groups. According to linear regression, the type of surgery, radiculopathy, and radiculitis explain the significant postoperative pain in up to 50% of cases.Conclusion Our study reveals a significant difference in opioid consumption between patients undergoing different surgical techniques. While these findings are valid for the studied population, the limitation in sample size highlights the need for further research. The implications of our findings on postoperative pain management and opioid use in spinal surgeries are significant and warrant continued investigation.
Keywords: spine; arthrodesis; neurosurgery; pain management; opioids